Red eye - KOMNENOU (Α. ΚΟΜΝΗΝΟΥ) A.; DESSIRIS (Α. ΔΕΣΙΡΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this article "red eye" syndrome is presented. It is described how to distinguish among the various ocular and periocular anatomic structures that could be causing redness of the eye (history, ophthalmic examination, type of redness). The most common causes of red eye (conjunctivits, KCS, glaucoma, uveitis) are discussed in details and the appropriate therapeutic treatments are proposed as well.